Klebsiella variicola and Klebsiella quasipneumoniae with capacity to adapt to clinical and plant settings - Esperanza Martínez-Romero; Nadia Rodríguez-Medina; Marilú Beltrán-Rojel; Jeiry Toribio-Jiménez; Ulises Garza-Ramos (Instituto Nacional de Salud Pública, 2017)
Objective. To compare the genetic determinants involved in plant colonization or virulence in the reported genomes of K. variicola, K. quasipneumoniae and K. pneumoniae. Materials and methods. In silico comparisons and Jaccard analysis of genomic data were used. Fimbrial genes were detected by PCR. Biological assays were performed with plant and clinical isolates. Results. Plant colonization genes such as cellulases, catalases and hemagglutinins were mainly present in K. variicola genomes. Chromosomal β-lactamases were characteristic of this species and had been previously misclassified. K. variicola and K. pneumoniae isolates produced plant hormones. Conclusions. A mosaic distribution of different virulence- and plant-associated genes was found in K. variicola and in K. quasipneumoniae genomes. Some plant colonizing genes were found mainly in K. variicola genomes. The term plantanosis is proposed for plant-borne human infections.